2022
DOI: 10.3390/sports10120201
|View full text |Cite
|
Sign up to set email alerts
|

Which of the Physiological vs. Critical Speed Is a Determinant of Modern Pentathlon 200 m Front Crawl Swimming Performance: The Influence of Protocol and Ergometer vs. Swimming Pool Conditions

Abstract: Background: Modern pentathlon includes horse riding, fencing, swimming, shooting and cross-country running. Events can last many hours during which the athletes face almost maximal energy and physiological demands, and fatigue. Early recognition and prevention of injuries and overuse syndromes can be achieved by refining the individual training loads. The purpose of the study was to determine which parameter could be the most accurate predictor of swimming working capacity determinants in pentathletes. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Therefore, these results may not be generalizable to a novice-level swimming population. Since maximal/peak physiological responses in water are comparatively different than land-based (i.e., cycle or treadmill) measures [ 13 , 18 , 30 , 31 ], an alternative paradigm was employed presently that utilized freestyle swimming performance time to establish “performance validity” as predicted by the swimming flume protocol. It was also expected that physiological responses to maximal swimming efforts in both the flume and pool were likewise controlled by the rate limiting links within the oxygen kinetic chain [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these results may not be generalizable to a novice-level swimming population. Since maximal/peak physiological responses in water are comparatively different than land-based (i.e., cycle or treadmill) measures [ 13 , 18 , 30 , 31 ], an alternative paradigm was employed presently that utilized freestyle swimming performance time to establish “performance validity” as predicted by the swimming flume protocol. It was also expected that physiological responses to maximal swimming efforts in both the flume and pool were likewise controlled by the rate limiting links within the oxygen kinetic chain [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using poolside and flume protocols have identified critical velocity and measures of swimming economy as accurate determinants of swimming performance. Although not a priority focus of the present investigation, these measures can accurately predict aerobic capacity and may demonstrate a greater utility and ability to assist with training program design than VO 2 max sw alone [ 13 , 18 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty years later, in 1984, Synchronized Swimming joined the Olympics, while Marathon Swimming (10-km race for men and women) was included in 2008 (www.worldaquatics.com/about). In parallel, research in physiology applied to swimming emerged in the beginning of the 20th century, trying to answer several questions that have arisen over the years, particularly focusing on locomotion and its contribution to health and athletic performance (Liljestrand and Stenström, 1920;Zacca et al, 2020;Demarie et al, 2022).Although so-called "filtered evidence" such as systematic reviews and meta-analyses evaluate and synthesize the literature, they draw from the base of the pyramid, specifically randomized controlled trials -RCTs, cohort studies, and case reports. Narrative reviews, when authored by "Experts" in the field, can also offer valuable insights and contributions.…”
mentioning
confidence: 99%
“…Eighty years later, in 1984, Synchronized Swimming joined the Olympics, while Marathon Swimming (10-km race for men and women) was included in 2008 ( www.worldaquatics.com/about ). In parallel, research in physiology applied to swimming emerged in the beginning of the 20th century, trying to answer several questions that have arisen over the years, particularly focusing on locomotion and its contribution to health and athletic performance ( Liljestrand and Stenström, 1920 ; Zacca et al, 2020 ; Demarie et al, 2022 ).…”
mentioning
confidence: 99%